"Growing up and growing old with HIV": HIV+ adolescents' experiences of disclosing statuses to romantic partners in Bulawayo, Zimbabwe. Issue 4 (1st October 2020) - Mlilo, Philani; Dziva, Cowen; Moyo, Vuyisile Precious; Ndondo, Nonhlanhla Lindelwe; Ndlovu, Zanele; Muyambo, Nkosinathi
Abstract : This article explores the experiences of HIV-positive adolescents disclosing their status to romantic partners in Bulawayo, Zimbabwe. Disclosure of HIV status continues to be one of the most pressing issues facing adolescents, especially those in relationships, yet health care workers have minimal tailored guidance on how to approach this except to encourage full disclosure. Motives for disclosure were: guilty conscience; legal and ethical obligations; preventing partners being infected; and supportive people, honesty and trust. Disclosure was done on a one-on-one basis in public spaces such as roadsides where the adolescents usually met, or in health care facilities through the help of health care workers, and through mobile phones using WhatsApp. Results revealed that disclosure was associated with negative and positive outcomes ranging from disruption of relationships, depression, breaches of confidential information and, in some instances, relationship and marriage assurance. However, results clearly showed that adolescents living with HIV struggle with disclosure because the process is complex and loaded with emotions and the outcomes can be unpredictable and difficult to handle. Optimism towards treatment, social support, rationalisation, and social comparison through attributing new meanings to the disease were employed to deal with negative outcomes of disclosure. Therefore, the development and implementation of evidence-based initiatives to raise awareness and train the youth to disclose is recommended. Through their experiences, we can learn what works well and what needs to be strengthened.